Barbados : Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
In this paper, the following statistical data are presented in detail: index of industrial production, selected sugar statistics, retail price index, nominal wage index, central government operations and transfers, operations of national insurance schemes, liquidity position of commercial banks, interest rates, operations of credit unions, summary accounts of offshore banks, balance of payments, selected interest rates, operations of credit unions, total exports and imports, services, investment income, current transfer, tourism statistics, capital account, summary of external debt, direction of trade, and so on.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet